2019
DOI: 10.1097/acm.0000000000002733
|View full text |Cite
|
Sign up to set email alerts
|

A Timely Problem: Parental Leave During Medical Training

Abstract: Shifting demographics and concerns about burnout prevention merit a reexamination of existing structures and policies related to leaves of absence that may be necessary during medical training. In this Invited Commentary, the authors address the issue of parental leave for medical students and residents. Discussion about parental leave for these trainees is not new. Despite decades of dialogue, leave policies throughout the undergraduate and graduate medical education continuum lack standardization and are cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Our results reveal variation in perceived support across programs in a single institution, similar to prior studies 17–21 . Trainees have inconsistent knowledge of parental leave policies and report frustration with conflicting messaging regarding duration of paid leave, vacation and elective eligibility, and requirements to extend training to maintain board eligibility.…”
Section: Discussionsupporting
confidence: 70%
“…Our results reveal variation in perceived support across programs in a single institution, similar to prior studies 17–21 . Trainees have inconsistent knowledge of parental leave policies and report frustration with conflicting messaging regarding duration of paid leave, vacation and elective eligibility, and requirements to extend training to maintain board eligibility.…”
Section: Discussionsupporting
confidence: 70%
“…6 Prior research has demonstrated many residency programs and institutions fail to provide comprehensive family leave to trainees or faculty. 11 However, to our knowledge, this is the first major review of current family leave policies for medical students studying in the United States and its territories.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an article with a description of parental leave policies during medical training was published and included a call to action in the medical profession (21). The results from this study and prior related work (7,8) support the need for similar recommendations in the veterinary profession and indicate that veterinarians want changes.…”
mentioning
confidence: 53%